Prospects for using Ganoderma lucidum (Curtis) P. Karst. for biological control of phytopathogenic fungi. Issue 1 (September 2021) - Pavlov, I N; Litovka, Y A; Makolova, P V; Timofeev, A A; Litvinova, E A; Enazarov, R Kh
Abstract: Antifungal, morphological and cultural properties of the Siberian and Abkhaz strains of the medicinal basidiomycete Ganoderma lucidum (Curtis) P. Karst were studied. A group of strains characterized by high growth rates in vitro on agar media (7.3-8.0 mm / day) and plant waste from timber processing (3.3-3.9 mm / day) was found. All strains of G. lucidum exhibited antifungal activity against phytopathogenic fungi; the degree of phytopathogen inhibition ranged from 10 to 58 %. Basidial rootrot fungi Heterobasidion and ascomycete fungi Bipolaris, Alternaria, Fusarium are the most sensitive to the presence of G. lucidum . The cultures most effectively limiting the phytopathogen development in the group of fast-growing Abkhaz strains (antifungal activity ranged from 21 to 58%) were identified. The high antifungal activity of strains on lignocellulosic substrates allows us to consider them as promising biocontrol agents for reducing the number, primarily, of basidial phytopathogens.